Alaska and adjoining territory. - U.S. Coast and Geodetic Survey (U.S. Coast and Geodetic Survey, 1887)
Map shows late nineteenth century Alaska boundaries, ice fields, settlements, coastal detail, volcanoes, and readings for the Bering Strait and Sea. Relief shown by hachures and spot heights. Depths shown by soundings. Inset: [Aleutian Islands]. Scale [ca. 1:3,000,000].